Study on the correlation between energy availability and subclinical menstrual disorders - Bingzheng, Z.; Zhuo, J.; Qihao, W.; Lunhao, B. (Frontiers in Nutrition, 2024)
Background: There are few studies on the correlation between energy availability (EA) and subclinical menstrual disorders (SMD) in female athletes. This study aims to explore the differences in EA between female athletes with eumenorrhea and those with SMD, and the correlation between EA and the occurrence of SMD.